A qualitative synthesis of video feedback in higher education. Issue 2 (17th February 2019) - Mahoney, Paige; Macfarlane, Susie; Ajjawi, Rola
ABSTRACT: While written and audio feedback have been well-examined by researchers, video feedback has received less attention. This review establishes the current state of research into video feedback encompassing three formats: talking head, screencast and combination screencast. Existing research shows that video feedback has a high level of acceptability amongst both staff and students and may help strengthen student-marker relationships; however, the impact of video feedback on student learning outcomes is yet to be determined. In addition, current evidence is drawn largely from small-scale studies and self-reported data susceptible to the novelty effect. While video feedback appears to be a promising alternative to traditional written feedback for its relative relational richness, the medium continues to be primarily used for information transmission rather than dialogue. Further research is needed to establish how the medium of video influences the feedback process, its potential to facilitate dialogue and its effects on student learning.